Effect of feeding Atlantic salmon (salmo salar L.) a diet inriched with stearidonic acid from parr to smolt on growth and lc-pufa biosynthesis - Mohamed Codabaccus; Nichols, P; Andrew Bridle; Christopher Carter (2009)
No description available